PENGUATAN UPAYA PENEGAKAN HUKUM “KEJAHATAN TERKAIT DENGAN PERIKANAN” MELALUI REGIONAL COOPERATION AGREEMENT AGAINST CRIMES RELATED TO FISHERIES - Ayu Mawar Rini (Mimbar Hukum - Fakultas Hukum Universitas Gadjah Mada, 2020)
AbstractThe research aims to analyse the urgency of the establishment of the Regional Cooperation Agreement Against Crimes Related to Fisheries. Considering the broad and emerging nature of Crimes Related to Fisheries, however, could not be solved accordingly by finding the recognition of IUUF as the form of Transnational Organized Crime. The initiative on establishing such agreement with the regional and market approach is trusted as the first practical solution taken by Indonesia to reduce the existence of Crimes Related to Fisheries, which at the same time strengthening the law enforcement for such crimes within the region. IntisariPenelitian ini bertujuan untuk menganalisa urgensi pembentukan “Perjanjian Kerjasama Regional Melawan Kejahatan Terkait dengan Perikanan”. Sifat “Kejahatan Terkait dengan Perikanan” yang luas serta terus berkembang tidak dapat serta merta diatasi dengan pengategorian IUUF sebagai bentuk dari Transnational Organized Crime. Inisiatif pembentukan perjnajian kerjasama dengan basis pendekatan kawasan dan pendekatan kawasan dipercaya mampu menjadi langkah awal bagi Indonesia serta menguatkan penegakan hukum untuk mengurangi kejahatan terkait di kawasan regional.